2020
DOI: 10.1101/2020.10.09.333815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fetal innate immunity contributes to the induction of atypical behaviors in a mouse model of maternal immune activation

Abstract: SummaryMaternal immune activation (MIA) increases likelihood of altered neurodevelopmental outcomes. Maternal cytokines are proposed to affect fetal brain development in mice; however, the contribution of fetal immunity to neurodevelopmental disorders is largely unexplored. Here, we show that MIA mediated by Toll-like receptor 3 (TLR3), but not other TLRs, induces a specific set of behavioral phenotypes including decreased sociability and increased restricted repetitive behavior in offspring. Accordingly, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Indeed, MIA induces an adaptive immune response in mothers, particularly the activation of a subset of T helper cells (Th17 T cells) and the release of maternal cytokines such as interleukin (IL)-17, that can affect fetal brain development in mice ( Choi et al, 2016 ). However, a few groups, including ours, have reported that MIA may also directly induce an inflammatory innate immune response in fetal myeloid cells ( Onore et al, 2014 ; Matcovitch-Natan et al, 2016 ; Carlezon et al, 2019 ; Ben-Yehuda et al, 2020 ; Cui et al, 2020 ; Nichols et al, 2020 , preprint).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, MIA induces an adaptive immune response in mothers, particularly the activation of a subset of T helper cells (Th17 T cells) and the release of maternal cytokines such as interleukin (IL)-17, that can affect fetal brain development in mice ( Choi et al, 2016 ). However, a few groups, including ours, have reported that MIA may also directly induce an inflammatory innate immune response in fetal myeloid cells ( Onore et al, 2014 ; Matcovitch-Natan et al, 2016 ; Carlezon et al, 2019 ; Ben-Yehuda et al, 2020 ; Cui et al, 2020 ; Nichols et al, 2020 , preprint).…”
Section: Introductionmentioning
confidence: 82%
“…This MIA-induced ASD model displays behavioral phenotypes, including decreased sociability, increased repetitive restricted behavior, impaired learning and memory, altered levels of anxiety, and hyperactivity ( Patterson, 2011 ; Estes and McAllister, 2016 ). Importantly, several groups have reported that the behavioral phenotypes in this model are only observed in male offspring ( Xuan and Hampson, 2014 ; Coiro and Pollak, 2019 ; Haida et al, 2019 ; Keever et al, 2020 ; Nichols et al, 2020 , preprint; Figure 1A ). Based on these findings, MIA induction in mice is widely used to study the mechanism of ASD because it successfully recaptures behavioral phenotypes and sex-specific features observed in the disorder.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation